2017
DOI: 10.1037/pac0000206
|View full text |Cite
|
Sign up to set email alerts
|

Toward identifying the etiologies of gender differences in authoritarianism and mental health: An Egyptian study.

Abstract: Compelling evidence of gender differences in authoritarianism, self-esteem, and mental disorders can be found in the psychology literature. However, researchers have not yet identified their etiologies. The traumatology perspective proposes that gender discrimination (GD) contributes to such differences. GD promotes internalized male superiority and enhanced self-esteem that increase authoritarianism and impact men's behavior. GD promotes internalized gender inferiority in women and decreased self-esteem, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Also, on different violated physical identities (e.g., life-threatening events), and on role identities. Empirical studies have focused on various violated collective identities including racial identity ethnic identity, Native American identity (e.g., Omidy, 2012), and gender identity (e.g., Kira et al, 2015;Kira, Shuwiekh, & Bujold-Bugeaud, 2017), and found that social identities violations are linked to adverse mental health outcomes. The results of meta-analyses (Pascoe & Smart Richman, 2009) have also supported significant positive associations between identity violations and internalizing and externalizing disorders, general distress, depressive symptoms, anxiety, substance abuse, anger, psychosis, as well as negative associations with happiness, life satisfaction, and mastery.…”
Section: C) the Dynamics Of Existential Anxieties Activationmentioning
confidence: 99%
“…Also, on different violated physical identities (e.g., life-threatening events), and on role identities. Empirical studies have focused on various violated collective identities including racial identity ethnic identity, Native American identity (e.g., Omidy, 2012), and gender identity (e.g., Kira et al, 2015;Kira, Shuwiekh, & Bujold-Bugeaud, 2017), and found that social identities violations are linked to adverse mental health outcomes. The results of meta-analyses (Pascoe & Smart Richman, 2009) have also supported significant positive associations between identity violations and internalizing and externalizing disorders, general distress, depressive symptoms, anxiety, substance abuse, anger, psychosis, as well as negative associations with happiness, life satisfaction, and mastery.…”
Section: C) the Dynamics Of Existential Anxieties Activationmentioning
confidence: 99%
“…It is noteworthy that gender discrimination can have negative impacts on mental status and health of an individual (Fischer & Holz, 2010;Klonoff et al, 1999;Landrine & Klonoff, 1997;Okechukwu et al, 2014). Perceived gender discrimination can be a major element in long-term anxiety and behavioral disorders (Kessler et al, 2005;Kira et al, 2017). A study conducted by Moradi and Subich (2003) addressed African American women and stated that sexist events can have a significant impact on psychological stress and this was seen even when other impacts of racist events have been controlled and taken account for.…”
Section: Sr-hrm and Perceived Discriminationmentioning
confidence: 99%
“…There is no doubt that the international community has a duty to prevent Assad from slaughtering even more Syrians and to bring him to trial for crimes against humanity. The study by Kira et al (2017) serves to highlight this continuing challenge.The last two major empirical articles are on moral themes: how individuals respond to moral transgressions by the ingroup (Kahn & Björklund, 2017) and by the outgroup (Nyarko & Punamäki, 2017). Moral transgressions of various kinds often take place in the course of conflict.…”
mentioning
confidence: 99%
“…There is no doubt that the international community has a duty to prevent Assad from slaughtering even more Syrians and to bring him to trial for crimes against humanity. The study by Kira et al (2017) serves to highlight this continuing challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation